2016
DOI: 10.1002/anie.201602512
|View full text |Cite
|
Sign up to set email alerts
|

Pt3Co Octapods as Superior Catalysts of CO2 Hydrogenation

Abstract: As the electron transfer to CO2 is a critical step in the activation of CO2 , it is of significant importance to engineer the electronic properties of CO2 hydrogenation catalysts to enhance their activity. Herein, we prepared Pt3 Co nanocrystals with improved catalytic performance towards CO2 hydrogenation to methanol. Pt3 Co octapods, Pt3 Co nanocubes, Pt octapods, and Pt nanocubes were tested, and the Pt3 Co octapods achieved the best catalytic activity. Both the presence of multiple sharp tips and charge tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
125
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(132 citation statements)
references
References 53 publications
7
125
0
Order By: Relevance
“…[12] Unfortunately, such high applied potential also causes Cu electrochemical migration, dissolution, and redeposition that sinter the Cu NPs. [3][4][5]7,12,14,15] Since the study showing a linear correlation between grain boundary (GB) density and CO 2 RR performance by Li et al, [16] GBs have been explored as highly active catalytic sites for both CO 2 RR and carbon monoxide reduction, which promoted the production of CO and formic acid. Numerous chemical modifications and nanostructuring approaches have led to improvements in product selectivity and catalytic activity.…”
Section: Doi: 101002/adma201805405mentioning
confidence: 99%
“…[12] Unfortunately, such high applied potential also causes Cu electrochemical migration, dissolution, and redeposition that sinter the Cu NPs. [3][4][5]7,12,14,15] Since the study showing a linear correlation between grain boundary (GB) density and CO 2 RR performance by Li et al, [16] GBs have been explored as highly active catalytic sites for both CO 2 RR and carbon monoxide reduction, which promoted the production of CO and formic acid. Numerous chemical modifications and nanostructuring approaches have led to improvements in product selectivity and catalytic activity.…”
Section: Doi: 101002/adma201805405mentioning
confidence: 99%
“…[3] To enhance the efficiency of energy conversion, rational design of highly active and robust electrocatalysts to strengthen the adsorption and activation of inert CO 2 is important, which can be boosted by the fundamental understanding of the correlations between structure and proper-ties. [4] To this end, numerous studies have focused on the understanding of the size,f acet, and alloying effects in electrochemical reduction of CO 2 . [5] Surface strain, which is generally generated by the lattice mismatch between different kinds of compositions and some twin structures like icosahedra, is present extensively in heterogeneous catalysts.…”
mentioning
confidence: 99%
“…As shown in Figure a, the first desorption peak could originate from physisorbed or weakly chemisorbed CO 2 , whereas the second peak was associated with strongly chemisorbed CO 2 . The peak position of CO 2 desorption was the highest for NSCNW‐3, suggesting that the CO 2 adsorption strength was largest on the NSCNW‐3 . As shown in Figure b, the Nyquist plots revealed that the NSCNW‐3 exhibited a smaller semicircle radius compared with the other catalysts, indicating the facilitated charge‐transfer process between the catalysts and electrolyte.…”
Section: Resultsmentioning
confidence: 92%